EVALUATION OF PANCASILA-BASED LEARNING IN THE MERDEKA CURRICULUM: A LITERATURE REVIEW OF AUTHENTIC, FORMATIVE, AND SUMMATIVE APPROACHES TO MEASURING STUDENTS' HOLISTIC COMPETENCE IN THE ERA OF INCLUSIVE EDUCATION - Rona Rona (Adisam Publisher, 2026)
This study aims to analyse the concepts, approaches, and implications of Pancasila Student Profile-based learning evaluation in the context of the Merdeka Curriculum implementation. This study uses library research methods by collecting and analysing various relevant theoretical and empirical sources on authentic, formative, and summative assessments in measuring students' holistic competencies. The results of the study show that the learning evaluation paradigm has transformed from a system of measuring cognitive outcomes alone to a comprehensive assessment model oriented towards balancing cognitive, affective, and psychomotor aspects. The authentic approach emphasises the importance of project-based and real-life assessments that reflect the application of Pancasila values; formative assessment serves to provide continuous feedback to build reflection and self-improvement; while summative assessment is a validation tool to objectively assess the achievement of final competencies. In the context of inclusive education, the combination of these three approaches plays an important role in creating an adaptive, fair, and diverse evaluation system for students. Thus, learning evaluation in the Merdeka Curriculum not only functions as an academic measurement tool but also as a means of character building and strengthening human values in the lifelong learning process.